Annular Ligament Reconstruction With Triceps Autograft for Chronic Radial Head Instability. Issue 1 (March 2016) - Marinello, Patrick G.; Wagner, Timothy; Styron, Joseph; Maschke, Steven; Evans, Peter J.
Abstract : We present a modification and revisit of the Bell Tawse technique for annular ligament reconstruction with triceps autograft for chronic radial head instability. In patients with instability stemming from an incompetent annular ligament, this technique has proved successful to restore stability to the proximal radial capitellar joint as an augment after ensuring normal boney anatomy. Through a lateral Kocher approach, an approximately 10 cm×4 mm strip of lateral triceps tendon is harvested as a free graft for the reconstruction. Following passing of the triceps autograft around the radial neck, it is sutured to a mini-Mitek suture anchor and is placed into a decorticated portion of the proximal ulna to recreate the annular ligament. Finally, we present 2 case illustrations where this technique was successfully used for chronic radial head instability. Abstract : Supplemental Digital Content is available in the text.